2021
DOI: 10.1039/d1fd00002k
|View full text |Cite
|
Sign up to set email alerts
|

Developing a triple helix approach for CO2 utilisation assessment

Abstract: Assessment of the sustainability of CO2 utilisation technologies should encompass economic, environmental and social aspects. Though guidelines for economic and environmental assessment of CO2 utilisation (CDU) have been presented, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Finally, the sustainability of CO 2 mitigation strategies in refineries ought to consider the social dimension alongside economic and environmental trade-offs. This could follow a triple helix approach, as recently advocated for CO 2 utilization assessment (McCord et al, 2021). Furthermore, the costs associated with the transition to net-zero should be managed in a socially equitable manner (GCCSI, 2020).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Finally, the sustainability of CO 2 mitigation strategies in refineries ought to consider the social dimension alongside economic and environmental trade-offs. This could follow a triple helix approach, as recently advocated for CO 2 utilization assessment (McCord et al, 2021). Furthermore, the costs associated with the transition to net-zero should be managed in a socially equitable manner (GCCSI, 2020).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Carbon neutrality is an urgent goal in the current age 59 65 . Many technologies for producing value-added products claim using CO 2 as the feedstock can reduce CO 2 emission, but this may not be necessarily true, since the power consumed to run the facility, to produce H 2 , and to drive the chemical reaction may generate an even larger CO 2 footprint than the one the technology aims to reduce 66 . Chen’s group has recently demonstrated that using CO 2 to synthesize methanol either via thermocatalysis or electrocatalysis is still generating several mol of new CO 2 when one mol of CO 2 is consumed under the current US energy structure, far from reaching carbon neutrality 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Social impacts are most commonly reported relative to the UN SDGs (Sustainable Development Goals; United Nations, 2015b) or GRI (Kühnen and Hahn, 2017;McCord et al, 2021;Stiching Global Reporting Initiative, 2021;Global Reporting Initiative). However, these are typically carried out around deployed operations rather than during R&D (Zimmermann and Schomäcker, 2017;McCord et al, 2021), a problematic characteristic considering the low TRL nature of many CCU processes. Failure to assess social sustainability at early project stages may lead to development and investment in socially unsustainable technologies.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…SIA primarily focusses on corporate social responsibility, and can be defined as; "the process of identifying the future consequences of current or proposed actions, which are related to individuals, organizations and social macro-systems" (Becker, 2001;McCord et al, 2021). Vanclay (2003), proposes that any developed guidelines should be derived from core values and principles (Vanclay, 2003) such as the UN SDGs (United Nations, 2015a).…”
Section: Social Impact Assessmentmentioning
confidence: 99%
See 1 more Smart Citation